Memories of Recent Past. Objectives and Results of Non-invasive Archaeological Research Project at KL Plaszow Memorial Site - Karski, Kamil; Różycki, Sebastian; Schwarz, Aleksander (Analecta Archaeologica Ressoviensia, 2017)
Debate about the possibilities of using interdisciplinary methods in investigations of labor and concentration camps of world war two is well embedded. In this cases, the archaeology is a mixture of sub-disciplines like Combat Archaeology, War Archaeology and Interment Archaeology as well as a Public Archaeology. Field researches, especially non-invasives ones are common practices. In recent years numerous archeological research project has taken place. Some of them were prepared for the investment activities and design of memorials and new museums. The main purpose of documentation, surveys, and excavation of this kind of sites is a preservation of architectural relicts and landscape, but also a supplementing the historical knowledge by authentic archaeological sources. In this paper, authors decided to present the results of archaeological research project prepared in 2016 by The Historical Museum of the City of Kraków (MHK) and the investigations of Rabbinical Commission for Jewish Cemeteries in the area of labor and concentration camp Plaszow. The archeological documentation and investigations were combined with extensive research and study of memorial sites in Poland and Europe, which served as the basis for the scenario of the exhibition and commemoration of KL Plaszow as a future memorial site’s institution.